2013
DOI: 10.5858/arpa.2012-0218-cr
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Fibroid Polyp of the Gallbladder Bearing a Platelet-Derived Growth Factor Receptor Alpha Mutation

Abstract: The inflammatory fibroid polyp (IFP) is a benign lesion occurring in the digestive tract, mostly in the stomach and small bowel, composed of fibrovascular tissue infiltrated by inflammatory cells including eosinophils and mastocytes. Its pathogenesis has been controversial (reactive versus neoplastic). The recent finding of mutations in platelet-derived growth factor receptor α (PDGFRA) in most gastric and small intestinal IFPs supported their neoplastic etiology, moreover helping in their differential diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…[ 34 ] Inflammatory fibroid polyps, although often arising in the gastric antrum, rarely grow deeper than submucosa, typically feature CD34+ spindle cells arranged in an onion-skin pattern around blood vessels, are rich in eosinophils and are often PDGRA mutant. [ 40 ] Schwannomas, although often displaying areas with a loose texture (so-called “Antoni B areas”) and sometimes featuring a plexiform architecture, often exhibit peripheral lymphoid aggregates and are consistently intensely and diffusely S100+. Inflammatory myofibroblastic tumors feature a relevant inflammatory infiltrate which, together with the loosely arranged myofibroblasts in an edematous myxoid background, simulates granulation tissue; moreover, about half of cases display cytoplasmic positivity for ALK protein.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Inflammatory fibroid polyps, although often arising in the gastric antrum, rarely grow deeper than submucosa, typically feature CD34+ spindle cells arranged in an onion-skin pattern around blood vessels, are rich in eosinophils and are often PDGRA mutant. [ 40 ] Schwannomas, although often displaying areas with a loose texture (so-called “Antoni B areas”) and sometimes featuring a plexiform architecture, often exhibit peripheral lymphoid aggregates and are consistently intensely and diffusely S100+. Inflammatory myofibroblastic tumors feature a relevant inflammatory infiltrate which, together with the loosely arranged myofibroblasts in an edematous myxoid background, simulates granulation tissue; moreover, about half of cases display cytoplasmic positivity for ALK protein.…”
Section: Discussionmentioning
confidence: 99%
“…KIT (exons 9, 11, 13, and 17) and PDGFRA (exons 12, 14, and 18) genes were amplified using the same primers and PCR conditions described elsewhere. [16][17][18] Further details are reported in Supplementary Materials and Methods.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…No physiological counterpart has hitherto been described for IFPs, although it has been suggested that they may develop from PDGFRA‐positive mesenchymal cells found along the villus membrane in the small intestine 2, 4. Conversely, GISTs as a whole are commonly considered to be related to interstitial cells of Cajal (ICCs) 5.…”
Section: Introductionmentioning
confidence: 99%